Assuring safety in an air traffic control system with defeasible logic programming - Gómez, Sergio Alejandro (2014)
Assuring safety in complex technical systems is a crucial issue in several critical applications like air traffic control or medical devices. We present a preliminary framework based on argumentation for assisting flight controllers to reach a decision related to safety constraints in an ever changing environment in which sensor data is gathered at real time.